2017
DOI: 10.17533/udea.le.n88a05
|View full text |Cite
|
Sign up to set email alerts
|

On the estimation of the price elasticity of electricity demand in the manufacturing industry of Colombia

Abstract: This paper presents an estimation of the reaction of electricity demand to changes in price levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(26 reference statements)
0
4
0
2
Order By: Relevance
“…This contradicts the results of previous studies (such as [23]) that found energy prices to be a key determinant for explaining GHG emissions. The rigid price elasticity of demand of fuels [46,47] shows that consumers would not react to price changes in the short term. Nevertheless, increased fuel prices may produce a substitution to more efficient or cheaper fuels in the long term, affecting accordingly carbon intensities and GHG emissions.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts the results of previous studies (such as [23]) that found energy prices to be a key determinant for explaining GHG emissions. The rigid price elasticity of demand of fuels [46,47] shows that consumers would not react to price changes in the short term. Nevertheless, increased fuel prices may produce a substitution to more efficient or cheaper fuels in the long term, affecting accordingly carbon intensities and GHG emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, various empirical studies have found evidence that the elasticity of demand is close to zero in electricity markets (Burke and Abayasekara, 2018;Zhu et al, 2018). Barrientos et al (2018) and Perez et al (2016) found similar evidence in Colombia; following the Weyl-Fabinger model, this evidence implies that pass-through in competitive electricity markets should be close to unity.…”
Section: Theoretical Framework Of Pass-through In Retail Marketsmentioning
confidence: 95%
“…Specifically, with periodically collected measurements, Ski$S_{ki}$ and ρj$\rho _j$ could be estimated from the power flow model and the generation dispatch model, respectively [55, 56]. The same goes for the DR model and load forecast model [57, 58]. With these models and system measurements, we could calculate system states at the target time accordingly.…”
Section: Real‐time Pricing Response Attackmentioning
confidence: 99%